Thai Accountants’ Demand for Work Relocation under ASEAN Economic Community (AEC) Arrangement - Boontanomtirath, Pattamarnan; Sririthreeraphithak, Khomphat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The ASEAN Economic Community (AEC) was officially established at the end of past 2015 with a free labor mobility arrangement enforced under the Mutual Recognition Arrangement (MRA). The purpose of this research is to identify the factors affecting the demand of Thai accountant-related professionals to work within ASEAN-member countries. The study shows 68.46% of respondents having no interest in working as accountants in ASEAN countries. Of all the reasons, 53.57% of them lack proficiency in English, 46.79% are satisfied with their present salaries and fringe benefits in Thailand, and 46.43% have family and age constraints. Of all the respondents, 31.54% are interested in working with firms in AEC. Of these, 77.51% prefer to have working experience abroad, 69.99% are to have higher salaries, and 69.77% expect professional progress. Topping those who are interested in work relocation are management accountants. In contrast, tax accountants demand smallest work relocation, due to different tax laws and regulations within ASEAN countries. Besides, 73.64% of Thai accountants prefer to work in Singapore and 37.98% would like to work in Malaysia. At a 0.05 level of significance, sex, status and age have strong influence on work relocation decision while education has insignificant influence.